An efficient identity-based group signature scheme over elliptic curves - Han, Song; Liu, Wan-Quan (Springer, 2004)
Group signatures allow every authorized member of a group to sign on behalf of the underlying group. Anyone except the group manager is not able to validate who generates a signature for a document. A new identity-based group signature scheme is proposed in this paper. This scheme makes use of a bilinear function derived from Weil pairings over elliptic curves. Also, in the underlying composition of group signatures there is no exponentiation computation modulo a large composite number. Due to these ingredients of the novel group signatures, the proposed scheme is efficient with respect to the computation cost in signing process. In addition, this paper comes up with a security proof against adaptive forgeability.